A new formulation of oxalic acid for Varroa destructor control applied in Apis mellifera colonies in the presence of brood - Maggi, Matías (2015)
An organic product based on oxalic acid was evaluated for use inVarroacontrol under spring/summer climatic conditions in Argentina. The formulation consists of four strips made of cellulose impregnated with a solution based on oxalid acid. Forty-eight beehives were used to assess the product efficacy. Residues of the product were also tested in honey, bees, and wax. Each trial had respective control groups without oxalic treatment. At the beginning of the experiment, four strips of the formulation were applied to the colonies belonging to the treated group. Falling mites were counted after 7, 14, 21, 28, 35, and 42days. After the last count, the strips were removed and colonies received two flumethrin strips for 45days. Falling mites were counted throughout this period. Average efficacy of the organic product was 93.1% with low variability. This product is an organic treatment designed forVarroacontrol during brood presence and represents a good alternative to the synthetic treatments.